Mempertegas Pancasila Sebagai Ideologi Bangsa - Almas'udah Almas'udah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract: As a national consensus, Pancasila is an open and dynamic view of Indonesian life. The nature of the openness of Pancasila can be seen in the content of Pancasila which is a combination of diverse Indonesian values and universal values. The universality of Pancasila can be seen in the spirit of Godhead, humanity, justice, civilization, Indonesia (Indonesian unity), the spirit of mutual cooperation and social justice. Understanding the important function of Pancasila, it is necessary to revitalize the meaning, role and position of Pancasila for Indonesia's future as a modern state. The need for Pancasila revitalization is based on the belief that Pancasila is the most appropriate national node for a pluralistic Indonesia. One way to preserve the Pancasila paradigm is the rejuvenation (rejuvenation of the paradigm). Pancasila can be started by making Pancasila a public discourse. Thus, at the same time reassessment can be made on the meaning of Pancasila so far, to later produce new thoughts and meanings. Thus, making Pancasila as a public discourse is an important stage for the re-development of Pancasila as an open ideology that can be interpreted continuously so that it remains relevant in the life of the nation and state. The Pancasila mission for Indonesia is: to manage Indonesia (which is plural) in order to become a home for all the people who build it, and want to live quietly in it. This mission must also be a starting point for legal missions in the Indonesian context